木天蓼子가 LPS로 유되된 Mouse BV2 Microglial cells의 염증반응에 미치는 영향 - 김기태(Kitae Kim) (동의생리병리학회지, 2022)
Actinidia polygama has long been used in traditional Korean medicine to treat rheumatoid arthritis and gout. Although numerous chemical compounds in the fruit extracts of A. polygama have been characterized and their role in inhibiting nitric oxide (NO) production has been reported, the anti-inflammatory properties of A. polygama extracts remain to be explored. In this study, we investigated the in-vivo effect of A. polygama extract on lipopolysaccharide (LPS)-induced inflammation in BV-2 microglial cell lines. We discovered that 100% ethyl alcohol extract of A. polygama effectively attenuates the release of NO and is superior to both water extract and 50% ethanol extract. Using MTT assay, western blot, and ELISA on LPS-induced BV-2 microglial cells lines, we established the ability of A. polygama extract to markedly suppress the expressions of inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), and pro-inflammatory cytokines, such as tumor necrosis factor alpha and interleukin-6. These results reveal that the anti-inflammatory property of A. polygama in BV-2 microglial cells is due to the downregulation of iNOS, COX-2, MAPK protein, and pro-inflammatory cytokines. KCI Citation Count: 0